(untitled) (American Journal of Islam and Society, 1986)
Translation In the name of Allah, most benevolent, ever-merciful. Generations before you We destroyed when they Did wrong: their Apostles Came to them with Clear Signs, But they would not believe! Thus do We requite Those who sin! Surah X:13 Now such were their houses, - In utter ruin,-because They practised wrong-doing. Verily in this is a Sign For people of knowledge. And We saved those Righteousness Surah XXVII:52-53 We have revealed for you (O men!) a book in which Is a Message for you: Will ye not then understand? How many were the populations we utterly destoryed because Of their iniquities, setting up In their places other peoples? Surah XXI:10-11 Such were the populations we destroyed when they Commited iniquities; but we fixed an appointed time For their destruction. Surah XVIII:59